Stock Market Reaction to Corporate Sukuk Issuance: Evidence from Indonesia - Aisy, Fathiya Nimatul; Fianto, Bayu Arie (Universitas Airlangga, 2025)
This study aims to examine the reaction of the Indonesian stock market to sukuk issuances over an 11-year period from January 2013 to December 2023. The quantitative approach is employed using an event study and market model, with the Indonesia Sharia Stock Index (ISSI) as the benchmark. This study analyzes market reactions using average abnormal returns and average trading volume activity as variables. The results show that there is a market reaction around the sukuk issuance date, with a significant negative average abnormal return in periods t-7, t+2, and t+4. Furthermore, there is no significant difference in average abnormal returns and average trading volume activity before and after the sukuk issuance. The average abnormal return and average trading volume activity of each company also show no significant difference before and after the sukuk issuance, except for the average trading volume activity of companies TINS and INKP in the basic materials sector. These findings indicate a significant negative reaction to sukuk issuances. This result contradicts previous literature that states a significant market reaction, either positive or negative. The insignificance of these results seems to be caused by investor perceptions of sukuk issuances in Indonesia.